Use of residual herbicides in soybean and impact on corn in succession - Constantin, Jamil; Biffe, Denis Fernando; Oliveira Jr., Rubem Silvério de; Rosa, Ênio Lemes; Gheno, Eliezer Antonio; Machado, Fellipe Goulart; Pereira Braz, Guilherme Braga (Comunicata Scientiae, 2018)
The weed resistance to herbicides has generated the need to adopt different management strategies, listing the tank mixture applications and use of herbicides in different modalities. In this context, it is essential to evaluate the selectivity of these herbicides associations for the crop in which the positioning is performed, as well as the effect of the residual activity of these affecting the crop sown in succession. The objective of this study was to evaluate the control efficacy and selectivity of herbicides applied in pre and post-emergence in soybeans, and the effect of the residual activity of these products on corn cultivated in succession. Two experiments were conducted in field conditions, one for evaluating the effectiveness of the herbicides associations on weed control in soybeans and another to check the selectivity of these for soybeans and the carryover effect for corn cultivated in succession. The experimental design used in both experiments was the completely randomized blocks evaluating nine treatments. All treatments presented efficacy in the control of B. pilosa, D. horizontalis, and C. echinatus. Reductions in soybean yields were observed with the application of diclosulam (25.2 g ha-1) in pre or post-emergence. The association among glyphosate + trifluralin + cloransulam (720 + 1350 + 33,6 g ha-1) caused reductions in soybean yield. None of the treatments used in soybeans affected the corn yield grown in succession.